2019
DOI: 10.5607/en.2019.28.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Mitochondria in a Non-human Primate Model of MPTP-induced Parkinson's Disease: Drp1 and CDK5/p25 Signaling

Abstract: Mitochondria continuously fuse and divide to maintain homeostasis. An impairment in the balance between the fusion and fission processes can trigger mitochondrial dysfunction. Accumulating evidence suggests that mitochondrial dysfunction is related to neurodegenerative diseases such as Parkinson's disease (PD), with excessive mitochondrial fission in dopaminergic neurons being one of the pathological mechanisms of PD. Here, we investigated the balance between mitochondrial fusion and fission in the substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 68 publications
3
25
0
Order By: Relevance
“…Recently, accumulating evidence has demonstrated that inhibition of Drp1 and/or phospho-Drp1 Ser616 ameliorates neurotoxicity and deficits in dopamine release in PD animal models. Simone et al showed that treatment with mdivi-1, a putative inhibitor of Drp1, decreased mitochondrial dysfunction and oxidative stress in α-synuclein-overexpressing rats (Bido, Soria, Fan, Bezard & Tieu, 2017;Mishra, Singh, Tiwari, Bano & Shukla, 2019;Park et al, 2019). Our findings demonstrate that MPTP-induced mitochondrial fission was significantly weaker after SA treatment through decreased protein expression of phospho-Drp1 Ser616 and is correlated with recovery of mitochondrial function.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, accumulating evidence has demonstrated that inhibition of Drp1 and/or phospho-Drp1 Ser616 ameliorates neurotoxicity and deficits in dopamine release in PD animal models. Simone et al showed that treatment with mdivi-1, a putative inhibitor of Drp1, decreased mitochondrial dysfunction and oxidative stress in α-synuclein-overexpressing rats (Bido, Soria, Fan, Bezard & Tieu, 2017;Mishra, Singh, Tiwari, Bano & Shukla, 2019;Park et al, 2019). Our findings demonstrate that MPTP-induced mitochondrial fission was significantly weaker after SA treatment through decreased protein expression of phospho-Drp1 Ser616 and is correlated with recovery of mitochondrial function.…”
Section: Discussionsupporting
confidence: 53%
“…We used three adult (12-year-old) female cynomolgus macaques ( Macaca fascicularis ), which were obtained from Suzhou Xishan Zhongke Laboratory Animal Co. (Suzhou, China) and maintained in individual indoor cages at the National Primate Research Center (NPRC) in the Korea Research Institute of Bioscience and Biotechnology (KRIBB), as described previously [ 21 , 22 ]. Animal was fed commercial monkey chow (Harlan, USA), supplemented with various fruits and water ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…MPTP increased the activity of cyclin-dependent kinase 5 (CDK5) in the mouse model of PD. CDK5 was shown to be involved in the regulation of autophagy to mediate neuronal cell death and neurotoxicity [ 206 , 207 , 208 , 209 ]. Studies reported that MPTP increased LC3-II in C6 glioma cells and mouse striatum cells through CDK5 activation [ 204 ].…”
Section: Translational Applications Of Melatonin Against Nddsmentioning
confidence: 99%